Enantioselective inhibition of human CYP2C19 by the chiral pesticide ethofumesate: Prediction of pesticide-drug interactions in humans - Perovani, Icaro Salgado; Mariano Bucci, Jade Lorena; Carrão, Daniel Blascke; Santos Barbetta, Maike Felipe; Moreira da Silva, Rodrigo; Lopes, Norberto Peporine; Moraes de Oliveira, Anderson Rodrigo [UNESP] (Elsevier, 2021)
Ethofumesate is a chiral herbicide that may display enantioselective behavior in humans. For this reason, the enantioselective potential of ethofumesate and its main metabolite ethofumesate-2-hydroxy to cause pesticide-drug interactions on cytochrome P450 forms (CYPs) has been evaluated by using human liver microsomes. Among the evaluated CYPs, CYP2C19 had its activity decreased by the ethofumesate racemic mixture (rac-ETO), (+)-ethofumesate ((+)-ETO), and (−)-ethofumesate ((−)-ETO). CYP2C19 inhibition was not time-dependent, but a strong inhibition potential was observed for rac-ETO (IC50 = 5 ± 1 μmol L−1), (+)-ETO (IC50 = 1.6 ± 0.4 μmol L−1), and (−)-ETO (IC50 = 1.8 ± 0.4 μmol L−1). The reversible inhibition mechanism was competitive, and the inhibition constant (Ki) values for rac-ETO (2.6 ± 0.4 μmol L−1), (+)-ETO (1.5 ± 0.2 μmol L−1), and (−)-ETO (0.7 ± 0.1 μmol L−1) were comparable to the Ki values of strong CYP2C19 inhibitors. Inhibition of CYP2C19 by ethofumesate was enantioselective, being almost twice higher for (−)-ETO than for (+)-ETO, which indicates that this enantiomer may be a more potent inhibitor of this CYP form. For an in vitro-in vivo correlation, the Food and Drug Administration's (FDA) guideline on the assessment of drug-drug interactions used in the early stages of drug development was used. The FDA's R1 values were estimated on the basis of the obtained ethofumesate Ki and distribution volume, metabolism, unbound plasma fraction, gastrointestinal and dermal absorption data available in the literature. The correlation revealed that ethofumesate probably inhibits CYP2C19 in vivo for both chronic (oral) and occupational (dermal) exposure scenarios.
Keywords: CYP inhibition; CYP2C19; Enantioselective; Ethofumesate; Human liver microsomes; Pesticide-drug interaction